Performance measurement systems and metrics: A framework for monitoring oil operations - Nouara, Adel; DeCoster, Rebecca (Cranfield University Press, 2013)
Oil operations involve high levels of capital equipment and high capacity production processes for which performance measures can assist with monitoring production throughout the oil industry stages. The approach taken in this paper is to utilise the lifecycle approach of asset management as well as organisational resource factors in an integrative manner. This research will examine the use of performance measurement in both private and public oil companies with a focus on Developing Countries. National Oil companies are of national economic importance in Developing Countries. Thus purpose of this paper is to develop a conceptual framework for performance measures of current and future oil operations and the associated asset management for field operations. The approach taken is to recognise the national context and strategic drivers and then to examine within this context the three areas of: Asset Management; Oil Operations (including Technology and Development; Management approaches; Partnerships) and Performance Outcomes.
Keywords: Performance Measurement; Performance Management; Asset Management